Financial Circuits of Im/mobility: Constraining, Confining, and Coercing Asylum Seekers Through Prepayment Technology - Bennani-Taylor, Sophie (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
This article explores how the entangled circulation of data, capital, and discourse generates regimes of im/mobility for migrant populations. It does so by examining how the UK’s Asylum Support Enablement (ASPEN) card—a technology used to disburse Home Office funds to asylum seekers—captures and circulates its users’ transactions in ways that constrain some forms of movement while coercing others. In doing so, this article traces how long-standing discourses of foreign bodies as a threat to the social order intersect with new technologies that enable the constant monitoring of where and when such bodies move. Following a “regimes of im/mobility” approach, this article draws attention to the specific relationships of power that enable some people to move within and across borders while containing or constraining others. It thus nuances the presumed universalism of “surveillance capitalism” by examining the contradictory logics that emerge when data extractive technologies are brought into the border-industrial complex. Furthermore, it seeks to trouble the taxonomic distinction between “monitoring” and “surveillance” by considering how technologies that are ostensibly designed to protect their users can have equally violent effects as those explicitly designed to confine and penalise.